2016
DOI: 10.18290/rpsych.2016.19.2-1en
|View full text |Cite
|
Sign up to set email alerts
|

Identity formation in unstable times

Abstract: The process of adolescence, including identity formation, differs significantly from what it was in previous generations. This is a consequence, among other things, of the demographic and economic changes that have taken place in recent years, locally as well as globally. This introduction is devoted to a review of these problems, and the current issue comprises texts addressing selected questions in detail. Some scholars identify groups of young people characterized by a tendency to consciously avoid making c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…As a result of demographic and economic transformations that have taken place in recent years in Europe and North America, the process of growing up, including identity formation, has changed significantly compared to previous generations (Arnett, 2000; Brzezińska & Cieciuch, 2016; Bynner, 2005). Research demonstrated a considerable delay and qualitative change (high exploration, low commitment) in identity development of emerging adults in many Western industrialized countries (Kroger et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of demographic and economic transformations that have taken place in recent years in Europe and North America, the process of growing up, including identity formation, has changed significantly compared to previous generations (Arnett, 2000; Brzezińska & Cieciuch, 2016; Bynner, 2005). Research demonstrated a considerable delay and qualitative change (high exploration, low commitment) in identity development of emerging adults in many Western industrialized countries (Kroger et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of demographic and economic transformations that have taken place in recent years in Europe and North America, the process of growing up, including identity formation, has changed significantly compared to previous generations (Arnett, 2000;Brzezińska & Cieciuch, 2016;Bynner, 2005).…”
Section: Identity Processes and Its Associations With Individual And mentioning
confidence: 99%
“…A positively resolved crisis of old age leads to a sense of inner integrity, which manifests itself in kindness towards others, high self-esteem, satisfaction with one's current life, a positive assessment of one's past life, coming to terms with the inevitability of death, curiosity about the world, and a willingness to share one's own thoughts and experiences with younger people (Brzezińska, Appelt, Ziółkowska, 2016). The unresolved crisis of this period leads to despair and is associated with the inability to come to terms with the fact of the approaching end of life and feelings of regret for missed or lost opportunities, as well as the dominance of a sense of bitterness, pessimism, and resistance to change (Brzezińska, Hejmanowski, 2016).…”
Section: Foster Parenting In Old Age As a Crisismentioning
confidence: 99%